2009
DOI: 10.1002/ange.200900234
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Hydrogen Adsorption by an Organic Microporous Crystal

Abstract: Aufnahmefähig: Die außergewöhliche Kristallstruktur von 3,3′,4,4′‐Tetra(trimethylsilylethinyl)biphenyl wurde untersucht. Durch Entfernen eingeschlossener Solvensmoleküle entsteht ein organischer Kristall mit einer weitmaschigen mikroporösen Struktur, die derjenigen von Zeolith A verblüffend ähnlich ist (siehe Bild). Experimente zur reversiblen Adsorption von Stickstoff oder Wasserstoff bei 77 K bestätigten, dass die Mikroporen permanent bestehen bleiben.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 73 publications
0
42
0
7
Order By: Relevance
“…On the other hand, similar research efforts have been devoted to find a viable host molecular framework to encapsulate greenhouse gases such as CO 2 [30][31][32][33][34][35] or air-pollutants such as NO 2 or potentially poisonous gases such as CO and NO in order to reduce their adverse effect on the earth's atmosphere. N 2 encapsulation [36][37][38] is another important research topic in view of the potential usage of it in different domains. A relatively less examined problem has been the viability of storing rare gas (Rg) atoms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, similar research efforts have been devoted to find a viable host molecular framework to encapsulate greenhouse gases such as CO 2 [30][31][32][33][34][35] or air-pollutants such as NO 2 or potentially poisonous gases such as CO and NO in order to reduce their adverse effect on the earth's atmosphere. N 2 encapsulation [36][37][38] is another important research topic in view of the potential usage of it in different domains. A relatively less examined problem has been the viability of storing rare gas (Rg) atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the thermal stability of the covalent architecture of PPS widened the accessible temperature range for molecular rotors up to 750-800 K; these temperatures are normally unattainable for porous molecular crystals, polymers, and MOFs. [11] Thanks to this high stability, extremely fast regimes can be reached at high temperatures (above 10 10 Hz, see the Supporting Information). To account for the further restriction of the linewidths together with the weakening of the spectral shoulders, fast fluctuations of the phenyl rings within each jump site must be included in the 1808 flip mechanism.…”
mentioning
confidence: 97%
“…Indeed, TTEB has a Brunauer-Emmett-Teller (BET) surface area of 278 m 2 g À1 and adsorbs 0.8 wt % of hydrogen gas at 77 K and 10 bar. [16] Another type of porosity, intrinsic porosity, is observed for compounds which contain defined cavities or voids in the molecules themselves, such as in cucurbiturils and calixarenes. Investigations showed that in their crystalline states accessible pores exist for gas adsorption.…”
mentioning
confidence: 99%
“…Therefore, McKeown and coworkers described a different approach: Instead of synthesizing new compounds, they rather searched the Cambridge Structural Database (CSD) for known compounds by setting some defined criteria, to find those which are potentially permanent porous. [16] They identified 3,3',4,4'-tetra(trimethylsilylethynyl)biphenyl (TTEB) as a potential porous material and investigated the compounds gas-sorption properties. Indeed, TTEB has a Brunauer-Emmett-Teller (BET) surface area of 278 m 2 g À1 and adsorbs 0.8 wt % of hydrogen gas at 77 K and 10 bar.…”
mentioning
confidence: 99%